Nutritional strategies to optimize training and racing in middle-distance athletes - Stellingwerff, T.; Boit, M. K.; Res, P. T. (Journal of Sports Sciences, 2007)
Middle-distance athletes implement a dynamic continuum in training volume, duration, and intensity that utilizes all energy-producing pathways and muscle fibre types. At the centre of this periodized training regimen should be a periodized nutritional approach that takes into account acute and seasonal nutritional needs induced by specific training and competition loads. The majority of a middle-distance athlete's training and racing is dependant upon carbohydrate-derived energy provision. Thus, to support this training and racing intensity, a high carbohydrate intake should be targeted. The required energy expenditure throughout each training phase varies significantly, and thus the total energy intake should also vary accordingly to better maintain an ideal body composition. Optimizing acute recovery is highly dependant upon the immediate consumption of carbohydrate to maximize glycogen resynthesis rates. To optimize longer-term recovery, protein in conjunction with carbohydrate should be consumed. Supplementation of -alanine or sodium bicarbonate has been shown to augment intra- and extracellular buffering capacities, which may lead to a small performance increase. Future studies should aim to alter specific exercise (resistance vs. endurance) and/or nutrition stimuli and measure downstream effects at multiple levels that include gene and molecular signalling pathways, leading to muscle protein synthesis, that result in optimized phenotypic adaptation and performance.